Global acceleration in rates of vegetation change over the past 18,000 years - Mottl, Ondřej; Flantua, Suzette G A; Bhatta, Kuber P; Felde, Vivian A; Giesecke, Thomas; Goring, Simon; Grimm, Eric C; Haberle, Simon; Hooghiemstra, Henry; Ivory, Sarah; Kuneš, Petr; Wolters, Steffen; et al. (Science (New York, N.Y.), 2021)
Global vegetation over the past 18,000 years has been transformed first by the climate changes that accompanied the last deglaciation and again by increasing human pressures; however, the magnitude and patterns of rates of vegetation change are poorly understood globally. Using a compilation of 1181 fossil pollen sequences and newly developed statistical methods, we detect a worldwide acceleration in the rates of vegetation compositional change beginning between 4.6 and 2.9 thousand years ago that is globally unprecedented over the past 18,000 years in both magnitude and extent. Late Holocene rates of change equal or exceed the deglacial rates for all continents, which suggests that the scale of human effects on terrestrial ecosystems exceeds even the climate-driven transformations of the last deglaciation. The acceleration of biodiversity change demonstrated in ecological datasets from the past century began millennia ago.